(untitled) (La U Investiga, 2020)
There are multiple factors of different nature that influence work performance, the same that lead to physical and psychological damage that interfere with the quality of care in case of negative repercussions. This research aimed to identify the factors that influence the work performance of health personnel who work in the Type C Health Center, Latacunga. From a methodological point of view, this study was quantitative / descriptive / with a field cross-section. The population under study was all the health personnel working in the Type C Health Center, Latacunga, working with 100% of the sample population since it was finite and specific. The restructured Font Roja questionnaire was applied, consisting of 26 dichotomous questions (affirmative and negative) that allowed identifying the degree of influence (high / medium / low) of the factors on the work performance of health personnel. Regarding the results, it was evidenced that the factor, work motivation, has a medium affectation in most of the personnel and with a considerably high percentage with respect to the workload, it should be said that the Nursing personnel excel in this aspect. It is concluded that the staff of the Type C Health Center, Latacunga would run the risk of having a low work performance since they presented significant results in the face of work motivation factors and mainly the work load since most of them represent the female sex, that is, both workload and household chores are added.